A Comparison Between Two Average Modelling Techniques of AC-AC Power Converters - Pawel Szczesniak (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
In this paper, a comparative evaluation of two modelling tools for switching AC-AC power converters is presented. Both of them are based on average modelling techniques. The first approach is based on the circuit averaging technique and consists in the topological manipulations, applied to a converters states. The second approach makes use of state-space averaged model of the converter and is based on analytical manipulations using the different state representations of a converter. The two modelling techniques are applied to a same AC-AC converter called matrix-reactance frequency converter based on buck-boost topology. These techniques are compared on the basis of their rapidity, quantity of calculations and transformations and its limitations.